Relationship Between Serum High Density Lipoprotein Levels and Urine Albumin Levels in Chronic Kidney Disease Patients at ODSK Provincial Hospital, North Sulawesi - Karin Keisya Jovinka Dandel; Murniato Tiho; Stefana Helena Margaretha Kaligis (CV. Publikasi Indonesia, 2026)
Chronic kidney disease (CKD) is a global health problem with an increasing prevalence and is estimated to be the fifth leading cause of death by 2040. The main cause of mortality in CKD is cardiovascular complications, particularly atherosclerosis. Damage to glomerular filtration causes urinary albumin, while High Density Lipoprotein (HDL) dysfunction disrupts the reverse transport of cholesterol and the antioxidant, anti-inflammatory, and vasoprotective properties of HDL. In CKD, changes in the quantity and quality of HDL and increased urinary albumin reflect vascular and renal damage. The research aims to determine the relationship between serum HDL levels and urinary albumin levels in patients with chronic kidney disease at the ODSK Provincial Hospital in North Sulawesi. Methods: The study design used was an observational analytical study with a cross-sectional approach. This study used primary data in the form of blood and urine samples from hemodialysis patients in November 2025. The study employed simple random sampling with a sample size of 30 patients who met the inclusion and exclusion criteria. Based on the results of Pearson's correlation test, a p-value of 0.237 (> 0.05) was obtained. There is no significant relationship between serum HDL levels and urinary albumin levels in chronic kidney disease at ODSK Provincial Hospital in North Sulawesi.